Enzymes That Scavenge Reactive Oxygen Species Are Down-Regulated Prior to Gibberellic Acid-Induced Programmed Cell Death in Barley Aleurone - Fath, Angelika (American Society of Plant Physiologists, 2001)
Gibberellins (GAs) initiate a series of events that culminate in programmed cell death, whereas abscisic acid (ABA) prevents this process. Reactive oxygen species (ROS) are key elements in aleurone programmed cell death. Incubation of barley (Hordeum vulgare) aleurone layers in H(2)O(2) causes rapid death of all cells in GA- but not ABA-treated layers. Sensitivity to H(2)O(2) in GA-treated aleurone cells results from a decreased ability to metabolize ROS. The amounts and activities of ROS scavenging enzymes, including catalase (CAT), ascorbate peroxidase, and superoxide dismutase are strongly down-regulated in aleurone layers treated with GA. CAT activity, protein, and Cat2 mRNA decline rapidly following exposure of aleurone layers to GA. In ABA-treated layers, on the other hand, the amount and activity of CAT and Cat2 mRNA increases. Incubation in ABA maintains high amounts of ascorbate peroxidase and superoxide dismutase, whereas GA brings about a rapid reduction in the amounts of these enzymes. These data imply that GA-treated cells loose their ability to scavenge ROS and that this loss ultimately results in oxidative damage and cell death. ABA-treated cells, on the other hand, maintain their ability to scavenge ROS and remain viable.